2015
DOI: 10.1104/pp.15.01172
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the C Terminus of RHD3 Has a Critical Role in Homotypic ER Membrane Fusion in Arabidopsis

Abstract: The endoplasmic reticulum (ER) consists of dynamically changing tubules and cisternae. In animals and yeast, homotypic ER membrane fusion is mediated by fusogens (atlastin and Sey1p, respectively) that are membrane-associated dynamin-like GTPases. In Arabidopsis (Arabidopsis thaliana), another dynamin-like GTPase, ROOT HAIR DEFECTIVE3 (RHD3), has been proposed as an ER membrane fusogen, but direct evidence is lacking. Here, we show that RHD3 has an ER membrane fusion activity that is enhanced by phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…5 predict that either faster cross-connection or slower tension drift will give statistically smaller polygons. In principle, this prediction can be experimentally tested by analysis of the ER when manipulating molecular factors that control ER geometry and dynamics (2,8,9,(29)(30)(31)(32)(33)(34)(35)(36). A more sophisticated model will take other biophysical processes into account.…”
Section: Discussionmentioning
confidence: 99%
“…5 predict that either faster cross-connection or slower tension drift will give statistically smaller polygons. In principle, this prediction can be experimentally tested by analysis of the ER when manipulating molecular factors that control ER geometry and dynamics (2,8,9,(29)(30)(31)(32)(33)(34)(35)(36). A more sophisticated model will take other biophysical processes into account.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of RHD3 leads to a reduced elongation of cells of the primary root (Stefano et al, 2012). At a subcellular level, the loss of RHD3 also reduces the formation of three-way junctions owing to the capacity of the protein to fuse membranes in a GTP-dependent fashion (Ueda et al, 2016). In this context, RHD3 functions analogously to similar membrane-associated dynamin-like GTPases, such as metazoan atlastin and yeast Sey1p Zhang et al, 2013;Yan et al, 2015).…”
Section: Er Dynamics Depend On the Cytoskeleton And Er-shaping Proteinsmentioning
confidence: 99%
“…In particular, overexpression of the C-terminal region of RHD3 (RHD3 amino acids 677-802) disrupts the ER network integrity; conversely, overexpression of the analogous Sey1p region (Sey1p amino acids 682-776) does not . Intriguingly, the C-terminal domain of RHD3 is phosphorylated, and it has been shown that kinase treatment of RHD3 induces oligomerization of this protein, which in turn may modulate its ER-shaping function (Ueda et al, 2016).…”
Section: Er Dynamics Depend On the Cytoskeleton And Er-shaping Proteinsmentioning
confidence: 99%
“…Samples were analyzed by nano‐flow reverse phase liquid chromatography followed by tandem MS, using a Triple TOF 5600+, essentially described as previously . Briefly, a capillary reverse phase HPLC‐MS/MS system composed of an Eksigent Ekspert nano‐LC 400 HPLC system (AB Sciex), which was directly connected to an AB Sciex quadrupole time‐of‐flight (QqTOF) TripleTOF 5600+ mass spectrometer in Trap and Elute mode.…”
Section: Methodsmentioning
confidence: 99%